SISTEM PENILAIAN KINERJA TENAGA PENDIDIK DAN TENAGA KEPENDIDIKAN BERBASIS WEB DI STEKOM SEMARANG - Arsito Ari Kuncoro; Eko Haryono; Paulus Hartanto (Elkom : Jurnal Elektronika dan Komputer, 2020)
STEKOM College which has branch campuses in several places. Employee performance appraisals are carried out by superiors and branch campus coordinators using Ms. Excel. The results of the performance assessment are sent to the staffing department via e-mail. The personnel department will recap the results of the performance appraisal to be conveyed to the leadership. This assessment process takes a long time and tends to be inefficient. In this study, a web-based Employee Performance Appraisal System was developed that can be accessed online by relevant appraisers at the central campus and STEKOM branch campuses. The System Development Method uses a Research and Development (R&D) approach. Assessment elements include 6 (six) aspects, namely: Service Orientation, Integrity, Commitment, Discipline, Cooperation and Leadership. The results of the performance appraisal of educators (lecturers) apart from being used internally as a measurement of lecturers' work behavior, can also be used externally for the assessment of work behavior when the lecturer makes Employee Performance Targets (SKP), as well as being used to assess the performance of education personnel. System modeling uses the Unified Modeling Language (UML). Making the source code program using the Hypertext Preprocessor (PHP) programming language with a web-based MySQL database using Notepad ++ software. The results obtained from the use of the employee performance appraisal system, performance reports can be obtained more quickly, making it easier for the staffing department to obtain data on employee performance appraisals effectively and efficiently.